Evaluation of Renal Functional Status Using Probe Renogram Technique and USG (TAJ: Journal of Teachers Association, 2009)
Renal disorder is one of the most common problems in Bangladesh. Probe renogram is a verysensitive, specific, non-invasive and cost-effective procedure for the evaluation of renalfunction. Ultrasonography gives good anatomical information. It is cheap, non-time consumingand non-invasive procedure that requires no extra-preparation for studying kidneys. Combinedrenogram and USG were found to be very useful techniques for the evaluation of kidney'sfunctions. Biochemical parameters do not reflect the appropriate functional status of individualkidneys. Probe-renogram could reveal precisely the renal differential function. Retrospectively129 patients were studied, of which 80 (62.02%) were male and 49 (37.98%) were female, agebetween 8-78 years had come at the NMC, Rajshahi during the period of April 2000 to July 2001for radionuclide renography. The main objective of the study was to evaluate the response ofcombined renogram and USG for preliminary screening of renal disorders in patients beforegoing to other high cost and invasive investigations. Renal obstructions were found in 42 (LK-2Gand RK-16) cases and functional impairment of varying degrees was in 55 patients. Results werecorrelated well with clinical findings and other available diagnostic parameters.doi: 10.3329/taj.v15i2.3907TAJ December 2002; Vol.15(2):56-58